2017
DOI: 10.18632/oncotarget.18072
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation signature of long noncoding RNA genes during human pre-implantation embryonic development

Abstract: DNA methylation have crucial roles in regulating the expression of developmental genes during mammalian pre-implantation embryonic development (PED). However, the DNA methylation dynamic pattern of long noncoding RNA (lncRNA) genes, one type of epigenetic regulators, in human PED have not yet been demonstrated. Here, we performed a comprehensive analysis of lncRNA genes in human PED based on public reduced representation bisulphite sequencing (RRBS) data. We observed that both lncRNA and protein-coding genes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Recent evidence demonstrates that nearly 98% of the genome transcripts in human are noncoding RNAs (ncRNA) [ 9 , 10 ], among which long noncoding RNAs (lncRNAs) are transcripts of longer than 200 nucleotides and have no protein coding potential [ 11 , 12 ]. More and more reports showed that lncRNAs have many kinds of biological functions involved in embryo development, immunoregulation, and tumor development [ 13 – 15 ]. Aberrant expression of lncRNAs is closely related with human diseases, especially in cancers [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence demonstrates that nearly 98% of the genome transcripts in human are noncoding RNAs (ncRNA) [ 9 , 10 ], among which long noncoding RNAs (lncRNAs) are transcripts of longer than 200 nucleotides and have no protein coding potential [ 11 , 12 ]. More and more reports showed that lncRNAs have many kinds of biological functions involved in embryo development, immunoregulation, and tumor development [ 13 – 15 ]. Aberrant expression of lncRNAs is closely related with human diseases, especially in cancers [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports show that lncRNAs have no protein-coding potential 6 . Increasing evidence demonstrates that lncRNAs exerted very important functions in various biological processes, including cell development, immune regulation, and especially tumorigenesis 7–9 . More and more reports indicate that dysregulation of lncRNAs was closely related to tumor development and progression in various cancers 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNA) are a class of transcripts whose length is longer than 200 nucleotides and have no protein coding potential [ 9 ]. Accumulating evidences show that noncoding RNAs (ncRNA) exert essential roles in all kinds of biological processes including development, immune and especially in tumorgenesis [ 10 – 13 ]. In cancers, lncRNAs have been demonstrated to regulate cell proliferation, migration, invasion and apoptosis by several mechanisms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%